2011
DOI: 10.1007/s10620-011-1922-5
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of CXCL12 by DNA Hypermethylation and Its Involvement in Gastric Cancer Metastatic Progression

Abstract: Collectively, our results suggest that the aberrant methylation of CXCL12 frequently occurs in the down-regulation of CXCL12 in gastric cancers and that it may play a role in the metastasis of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…In breast cancer [29] and gastric cancer [30] patients, a low expression of CXCL12 but not of CXCR4 was related to a decrease in the regional extension of the disease.…”
Section: Discussionmentioning
confidence: 91%
“…In breast cancer [29] and gastric cancer [30] patients, a low expression of CXCL12 but not of CXCR4 was related to a decrease in the regional extension of the disease.…”
Section: Discussionmentioning
confidence: 91%
“…The role of CXCR7 in gastric and small bowel cancer is poorly understood. CXCR7 transcripts have been detected in gastric cancer cells, including MGC-803, SGC-7901 and BGC-823 cells (37). In a previous study, Lee et al (2) reported that CXCR7 was differentially expressed in gastric adenocarcinoma tissues.…”
Section: Cxcr7 In Cancer Of the Gastrointestinal Systemmentioning
confidence: 97%
“…Interestingly, p38 MAPK inhibitors induced significant downregulation of multidrug resistance-1 gene expression, a well- Chemokine defined marker of resistance to chemotherapy, which possibly induced susceptibility to the cisplatin treatment in this model [119] . In a separate study, Zhi et al [120] examined the expression of CXCL12 in normal gastric tissue, gastric cancer cell lines, 35 primary gastric carcinomas and corresponding normal gastric tissues. They found that CXCL12 was downregulated in gastric cancer cell lines and patient samples of primary gastric carcinomas compared to normal samples.…”
Section: Stomachmentioning
confidence: 99%
“…They provided evidence to show that CXCL12 expression was inversely associated with lymph node metastasis and histological grade. They concluded the possible cause of this downregulation of CXCL12 expression to be hypermethylation of the CXCL12 promoter, as treatment of highly metastatic cancer cell lines with a demethylating agent impaired its invasive phenotype [120] . One possible explanation for this reduction in CXCL12 might be to permit CXCR4-expressing gastric cancer cells to sense a CXCL12 gradient from target lymph nodes or other organs, which would otherwise be masked by CXCL12 expressed by the cancer cells.…”
Section: Stomachmentioning
confidence: 99%
See 1 more Smart Citation